Educational Activity of Seniors in Rural Areas of Selected Central and Eastern European Countries in the Context of Active Ageing - Kowalska, Magdalena; Knapik, Wioletta; Luty, Lidia; Zioło, Monika (Przegląd Badań Edukacyjnych (Educational Studies Review), 2025)
The global demographic problems of today focus on population ageing. The process is far from uniform; some continents, their regions and countries age faster and at a larger scale than others. This is the case in Europe. The dynamic process of population ageing in former Eastern Bloc countries, such as Poland, Czechia, and Slovakia, which were investigated here, is relatively new because it was identified about a decade ago. The present article is founded on pilot surveys in these three countries. The results of this research concern the educational activity of the rural population aged 60 and over. Rural areas were chosen for the study because, despite the general abundance of learning opportunities for older people in Poland, Czechia, and Slovakia, rural areas have much less to offer in terms of education, including for seniors. It is, therefore, important to find out the opinions and needs of the older rural population. Educational activities are an important leisure option for seniors. At the same time, it plays an important role in increasing their social participation and enhance the social and cultural capital of local communities. It also helps combat ageism, i.e. stereotypes associated with senior citizens. Participation of older people in any form of education is a critical component of the active ageing concept.